2017
DOI: 10.4103/ijo.ijo_985_15
|View full text |Cite
|
Sign up to set email alerts
|

Managing multiple caterpillar hair in the eye

Abstract: Ophthalmia nodosa with vitreoretinal involvement is rare and may cause permanent loss of eye due to persistent inflammation of the eye. A young female patient having multiple caterpillar hair in the eye including cornea, anterior chamber, sclera, and pars plana presented with recurrent vitritis and pars planitis. Ultrasound biomicroscopy played a vital role and helped in localizing the hair embedded in the pars plana region which were managed by pars plana vitrectomy leading to complete recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 5 publications
0
15
0
Order By: Relevance
“…Reports on the toxicity of this insect can be found in medical and veterinary literature. Most cases are European or Indian, but toxicity by similar lepidopters (an order of insects that includes butterflies and moths) has also been reported in Australia…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reports on the toxicity of this insect can be found in medical and veterinary literature. Most cases are European or Indian, but toxicity by similar lepidopters (an order of insects that includes butterflies and moths) has also been reported in Australia…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that movement produced by pulse and respiration propels the setae. In the eye, ductions, iris movement and blinking probably contribute to hair migration . It has been recently reported that the accidental ingestion of similar caterpillars ( Ochrogaster lunifer ) induces fetal loss in pregnant mares.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ocular involvement may occur in the form of conjunctival nodule, keratoconjunctivitis, uveitis, focal cataract and endophthalmitis 1. The caterpillar cilia have a typical property of migrating deep into the tissue with time and causing low-grade chronic inflammation due to the release of toxin thaumetopoein 2. Therefore, careful removal of all the cilia is essential to prevent delayed complications like migration of these cilia in the posterior segment.…”
Section: Descriptionmentioning
confidence: 99%
“…Delayed onset of posterior segment inflammation ranging from weeks to years 1 , 5 , 9 , 10 from the caterpillar contact mandates a high index of suspicion. Specific history of insect injury is crucial to clinch the diagnosis, as often the fine setae or their broken barbs are invisible.…”
Section: Introductionmentioning
confidence: 99%